2019
DOI: 10.1002/cbdv.201800504
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Components and Antioxidant and Tyrosinase Inhibitory Activities of Styphnolobium japonicum (L.) Schott Extract during Flower Maturity Stages

Abstract: Styphnolobium japonicum (L.) Schott is widely cultivated in China, and its flowers and flower buds (FFB‐SJ) are commonly used as traditional Chinese medicine. This work aimed to assess variations in the chemical components and antioxidant and tyrosinase inhibitory activities of S. japonicum extract during five flower maturity stages (ES1–ES5). The results showed that the contents of total flavonoids, rutin, and narcissin were highest at ES1, whereas the contents of quercetin and isorhamnetin were highest at ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Rutin has several actions on the central nervous system namely in the prevention of neuroinflammation, promoting neural crest cell survival, it exhibits sedative, anti‐Alzheimer and anticonvulsant activities [31] . Interestingly, studies have also reported on the anti‐tyrosinase effect of rutin [32,33] . Docking analysis demonstrated that rutin interacts with the side chains of the key amino acid residues and to the copper atom found at the active site of tyrosinase [34] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rutin has several actions on the central nervous system namely in the prevention of neuroinflammation, promoting neural crest cell survival, it exhibits sedative, anti‐Alzheimer and anticonvulsant activities [31] . Interestingly, studies have also reported on the anti‐tyrosinase effect of rutin [32,33] . Docking analysis demonstrated that rutin interacts with the side chains of the key amino acid residues and to the copper atom found at the active site of tyrosinase [34] .…”
Section: Resultsmentioning
confidence: 99%
“…[31] Interestingly, studies have also reported on the anti-tyrosinase effect of rutin. [32,33] Docking analysis demonstrated that rutin interacts with the side chains of the key amino acid residues and to the copper atom found at the active site of tyrosinase. [34] Having said that, it can be assumed that the significant cholinesterase and tyrosinase activities demonstrated may be resulting from the high level of rutin present.…”
Section: Enzymatic Inhibitory Propertiesmentioning
confidence: 99%
“…The lectin activity and protein content of S. japonica also decrease as the flower buds mature ( Cholak et al, 2016 ). Our previous study showed that the flavonoid content in S. japonica extract varied across the five flower-maturity stages, along with variations in antioxidant and tyrosinase inhibition activities ( Wang et al, 2019 ). Candidate genes involved in anthocyanin biosynthesis in wild-type and mutant-type S. japonica during different developmental stages were identified based on transcriptomics by Guo et al (2022) .…”
Section: Introductionmentioning
confidence: 99%
“…FSI has been widely used for 2,000 years in China as an important traditional Chinese medicine, due to its antitumor, anti-inflammatory, and antibacterial activities ( Liu T. et al, 2019 ; Huang et al, 2020 ). Many studies have reported that the antioxidant compounds of FSI are responsible for its efficacy ( Yao et al, 2011 ; Zhang et al, 2011 ; Hu et al, 2016 ; Wang et al, 2019 ). Therefore, FSI may prevent the photodegradation of Monascus pigments in HQW during storage.…”
Section: Introductionmentioning
confidence: 99%